Phylogenomics of the killer whale indicates ecotype divergence in sympatry - Andre Moura; J. G. Kenny; R. R. Chaudhuri; M. A. Hughes; R. R. Reisinger; P. J. N. de Bruyn; M. E. Dahlheim; N. Hall; A. R. Hoelzel (2014)
For many highly mobile species, the marine environment presents few obvious barriers to gene flow. Even so, there is considerable diversity within and among species, referred to by some as the ‘marine speciation paradox’. The recent and diverse radiation of delphinid cetaceans (dolphins) represents a good example of this. Delphinids are capable of extensive dispersion and yet many show fine-scale genetic differentiation among populations. Proposed mechanisms include the division and isolation of populations based on habitat dependence and resource specializations, and habitat release or changing dispersal corridors during glacial cycles. Here we use a phylogenomic approach to investigate the origin of differentiated sympatric populations of killer whales (Orcinus orca). Killer whales show strong specialization on prey choice in populations of stable matrifocal social groups (ecotypes), associated with genetic and phenotypic differentiation. Our data suggest evolution in sympatry among populations of resource specialists.